2011
DOI: 10.1039/c0ce00988a
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric tungsten oxide nanobrushes via oriented attachment and Ostwald ripening

Abstract: Tungsten oxide nanobrushes were synthesized using a solvothermal approach that lead to self-branching in the presence of citric acid and hexadecylamine as surfactants. Our synthetic approach yielded branched nanorods of tungsten oxide in a single synthetic step. Based on our results, we propose a phenomenological pathway for the formation, branching, and assembly of these tungsten oxide brushes. The formation of tungsten oxide brushes proceeds by thermal decomposition of ammonium tungstate in the presence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Among those approaches, hydrothermal methods have shown obvious advantages and have been widely applied for fabrication of WO 3 nanostructures because of their rich modulating experimental parameters, such as the chemical composition of precursors, heating temperature, pressure of reaction environment and heating durations, etc. [18][19][20] Besides, the cheap equipment and simple operation further facilitate fabrication of nanomaterials. Researchers have prepared various kinds of WO 3 nanostructures with varying dimensions, architectures, and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Among those approaches, hydrothermal methods have shown obvious advantages and have been widely applied for fabrication of WO 3 nanostructures because of their rich modulating experimental parameters, such as the chemical composition of precursors, heating temperature, pressure of reaction environment and heating durations, etc. [18][19][20] Besides, the cheap equipment and simple operation further facilitate fabrication of nanomaterials. Researchers have prepared various kinds of WO 3 nanostructures with varying dimensions, architectures, and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we discuss it in detail based on the band structure and work functions. It was reported that the work functions (F) of WO 3 lm, metallic Pt, and metallic Ag are 5.7 eV, [45][46][47] 5.65 eV, 48 and 4.26 eV, 49 respectively. In addition, the work function of the bimetallic alloy can be expressed by the sum of the work functions of the two metal components, 50 which means that the work function of the alloy lies at a level intermediate between monometallic Pt and Ag (4.26 eV < F Pt-Ag < 5.65 eV).…”
mentioning
confidence: 99%
“…Similar morphology of different compositional architectures based on the formation of aggregation of nanoparticles has been synthesized by many groups . However, the formation mechanism and the growing process are still remaining unclear.…”
Section: Resultsmentioning
confidence: 98%